2014
DOI: 10.1080/10426914.2013.872262
|View full text |Cite
|
Sign up to set email alerts
|

Study of a New Method to Fabricate W–Cu Composites

Abstract: W-Cu composites were prepared by a method of combustion synthesis and melt-infiltration in an ultrahigh-gravity field. The effects of the ultrahigh-gravity factor, quantity of W powder bed and W particle size on the properties of the prepared W-Cu composites were investigated. The microhardness and thermal expansion coefficient increased with the increase of the ultrahigh-gravity factor, as the enhanced ultrahigh-gravity field resulted in higher cooling rate and subsequently the formation of more defects (e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Bulk material processing with low cost by liquid processing requires more attention. Researchers have put the effort in various casting routes [3][4][5][6][7][8][9][10][11][12][13][14][15], but limited literature is available for aluminium (Al) -MWCNT composites by casting. Mansoor et al [16], reported an instantaneous enhancement in tensile strength (52%), yield strength (77%), hardness (45%) and ductility (44%) on 0.2vol.% MWCNT reinforced aluminum composite, which is produced by induction melting.…”
Section: Introductionmentioning
confidence: 99%
“…Bulk material processing with low cost by liquid processing requires more attention. Researchers have put the effort in various casting routes [3][4][5][6][7][8][9][10][11][12][13][14][15], but limited literature is available for aluminium (Al) -MWCNT composites by casting. Mansoor et al [16], reported an instantaneous enhancement in tensile strength (52%), yield strength (77%), hardness (45%) and ductility (44%) on 0.2vol.% MWCNT reinforced aluminum composite, which is produced by induction melting.…”
Section: Introductionmentioning
confidence: 99%